Risk factors for developing diabetes after 3 years among community‐dwelling elderly with impaired fasting glucose. Issue 2 (24th July 2018) - Zhang, Wen; Yang, Xiaolong; Han, Peipei; Ma, Yixuan; Fu, Liyuan; Jia, Liye; Yu, Hairui; Chen, Xiaoyu; Wang, Lu; Hou, Lin; Yu, Xing; Kohzuki, Masahiro; et al.
Abstract: Background: The aim of the present study was to examine the risk factors for developing diabetes after 3 years in an elderly Chinese suburban population with impaired fasting glucose (IFG). Methods: The study population comprised residents of the Hangu area of Tianjin, China, with IFG, aged ≥60 years, who joined the national free physical examination program ( n  = 328; mean [±SD] age 68.0 ±6.1 years; 48.2% men). Diabetes was defined by self‐report of a physician's diagnosis or fasting plasma glucose (FPG) ≥7.0 mmol/L; IFG was defined as FPG ≥5.6 and < 7.0 mmol/L. Risk factors of incident diabetes at the 3‐year follow‐up were analyzed individually using logistic regression analysis. Results: Between baseline and the 3‐year follow‐up, 56 subjects with IFG at baseline had developed diabetes. After multivariate adjustment for demographic and clinical factors, the incidence of diabetes increased with higher FPG (odds ratio [OR] 9.30, 95% confidence interval [CI] 2.84–30.48), but decreased with the grip strength/weight ratio (OR 0.88, 95% CI 0.82–0.94). Moreover, the combination of higher FPG and lower grip strength/weight was associated with a higher incidence of diabetes than higher FPG only or lower grip strength/weight ( P  < 0.05). Conclusion: The present study indicates that higher FPG and lower muscle strength are associated with glycemic deterioration among subjects with IFG after 3 years. The results suggest that not only glucose levels, but also physical performance may be useful markers of the risk of diabetes in this population. Abstract : Highlights This study showed that glucose levels and physical performance may be useful markers of risk in community‐dwelling elderly with impaired fasting glucose (IFG). This indicates that a better understanding of the factors potentially responsible for the increase in type 2 diabetes mellitus can help policy makers make decisions about diabetes prevention programs and policies.